Influence of mineral additions on the recycled aggregate concrete - Nor Aisyah Binti Jusoh (School of Environmental Engineering, University Malaysia Perlis, 2011)
Used of Recycled Aggregate (RA) in concrete can be described in environmental protection and economical terms. The application of recycled aggregate to use in construction activities have been practice by developed European countries and also of some Asian countries. This paper reports the results of an experimental study on the mechanical properties of Recycled Aggregate Concrete (RAC) as compared to Natural Aggregate Concrete (NAC). The effects of size Ra on compressive strenght wereinvestigate in this study.